Enhancing School Safety through Women’s Leadership: Insights from the Nepalese Community Schools (International Journal of Atharva, 2025)
This qualitative study explores the role of women’s leadership in fostering safer and more inclusive School environments in Nepalese community Schools. Guided by two key questions, the research examines how gender-inclusive leadership strategies enhance School safety and what systemic reforms are needed to support women in these roles. Drawing on case studies from three Schools in Kathmandu Valley, complemented by a focus group discussion with five additional female Principals, the study highlights the lived experiences and day-to-day leadership practices of women in education.Findings reveal that female Principals often adopt empathetic, collaborative, and student-centered approaches that enable them to respond effectively to complex issues such as gender-based violence, domestic abuse, and economic hardship. Many students, especially girls, felt more comfortable confiding in female leaders, leading to timely interventions and renewed access to education. These insights affirm the unique contributions of women’s leadership, aligning with feminist and transformational leadership theories. The study calls for supportive policies, mentorship, and professional development to empower more women to lead. By centering women’s voices and experiences, this research contributes to the growing conversation on gender equity in educational leadership and underscores the urgent need for structures that support both student well-being and inclusive School governance.